Improved liver diffusion-weighted imaging at 3 T using respiratory triggering in combination with simultaneous multislice acceleration - Tavakoli, Andrej; Attenberger, Ulrike; Budjan, Johannes; Schönberg, Stefan; Riffel, Philipp (Investigative radiology, 2019)
ObjectivesThe aim of this study was to retrospectively compare optimized respiratory-triggered diffusion-weighted imaging with simultaneous multislice acceleration (SMS-RT-DWI) of the liver with a standard free-breathing echo-planar DWI (s-DWI) protocol at 3 T with respect to the imaging artifacts i